STUDI KASUS : ASUHAN KEPERAWATAN PADA NY T 29 TAHUN P2A0 POST SEKSIO SESAREA ATAS INDIKASI PREEKLAMPSIA BERAT (PEB) DI RUMAH SAKIT HERMINA DEPOK - Retno Winarti; Rika Gisela; Suryani Hartati (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2023)
Preeclampsia can increase the maternal mortality rate by 26.47% per 100,000 live births, so it is necessary to carry out medical and nursing management that is fast and appropriate. The purpose of the case study in Scientific Paper is to describe the implementation of nursing care in patients with post-cesarean section for indications of severe preeclampsia using a case study approach. The research location was Hermina Hospital Depok on 13-17 March 2023. This research was conducted on Ny. T 29 Years P2A0. The results of the study found that the patient had dizziness, shortness of breath, pain on a scale of 5, an increase in weight of 25 kg during pregnancy, and the baby was treated separately. The diagnosis made by hypervolemia, acute pain, risk of infection, and ineffective breastfeeding. Actions taken are monitoring fluid balance, foot massage, early mobilization, and oketani massage. The results of the nursing evaluation found that the diagnosis of hypervolemia was resolved, acute pain was resolved, the risk of infection was not actual, and breastfeeding was not effectively resolved. The conclusion of the research the author has carried out nursing care according to the stages, actual nursing problems are resolved and potential nursing problems are not actual. Research suggestions on the process of nursing care are that nurses can apply foot massage to post-cesarean section patients, and oketani massage applications for relaxation and increased milk production.